ND

Chứng minh các hằng đẳng thức:

a) a3+b3+c3 - 3.a.b.c = ( a+b+c). ( a2+b2+c2 - a.b - b.c - a.c)

b) (a+b+c)3-a3-b3-c3 = 3.(a+b) . (b.c) . (c+a)

NT
26 tháng 11 2022 lúc 22:11

a:\(a^3+b^3+c^3-3abc\)

\(=\left(a+b\right)^3+c^3-3ab\left(a+b\right)-3abc\)

\(=\left(a+b+c\right)\left(a^2+2ab+b^2-ac-bc+c^2\right)-3ab\left(a+b+c\right)\)

\(=\left(a+b+c\right)\cdot\left(a^2+b^2+c^2-ab-ac-bc\right)\)

b: \(=\left(a+b+c-a\right)\left[\left(a+b+c\right)^2+a\left(a+b+c\right)+a^2\right]-\left(b+c\right)\left(b^2+bc+c^2\right)\)

\(=\left(b+c\right)\left(a^2+2ab+b^2+c^2+2ac+2bc+a^2+ab+ac+a^2-b^2-bc-c^2\right)\)

=3(a+b)(b+c)(a+c)

Bình luận (0)

Các câu hỏi tương tự
HA
Xem chi tiết
NB
Xem chi tiết
PV
Xem chi tiết
LC
Xem chi tiết
HN
Xem chi tiết
PL
Xem chi tiết
LT
Xem chi tiết
HP
Xem chi tiết
VA
Xem chi tiết
NH
Xem chi tiết